Explaining intra-monthly consumption patterns: The timing of income or the timing of consumption commitments? - Nathanael Vellekoop (Goethe University Frankfurt, SAFE - Sustainable Architecture for Finance in Europe, 2018)
A number of recent studies have concluded that consumer spending patterns over the month are closely linked to the timing of income receipt. This correlation is interpreted as evidence of hyperbolic discounting. I re-examine patterns of spending in the diary sample of the U.S. Consumer Expenditure Survey, incorporating information on the timing of the main consumption commitment for most households their monthly rent or mortgage payment. I find that non-durable and food spending increase with 30-48% on the day housing payments are made, with smaller increases in the days after. Moreover, households with weekly, biweekly and monthly income streams but the same timing of rent/mortgage payments have very similar consumption patterns. Exploiting variation in income, I find that households with extra liquidity decrease non-durable spending around housing payments, especially those households with a large budget share of housing.
Keywords: D12; D14; E21; 330; consumption; consumption commitments; paycheck frequency; liquidity